«Támbico pilar»: ¿un eco precolombino en Calderón de la Barca? - Sánchez Jiménez, Antonio (Edizioni Ca’ Foscari, 2021)
This short article analyses an apparent hapax (“támbico pilar”) in an auto sacramental by Pedro Calderón de la Barca, La cena del rey Baltasar (c. 1630-1635). After presenting the passage and the critics’ opinion on the subject, this essay contextualises the phrase and formulates a hypothesis to clarify the passage by using, among other arguments, other seventeenth-century printed texts.